Genomic epidemiology of methicillin-susceptible Staphylococcus aureus across colonisation and skin and soft tissue infection - Grinberg, A.; Biggs, P.; Zhang, J.; Ritchie, S.; Oneroa, Z.; O'Neill, C.; Karkaba, A.; Velathanthiri, N.; Coombs, Geoffrey (W.B. Saunders Co. Ltd., 2017)
Objectives: Staphylococcus aureus skin and soft tissue infection (Sa-SSTI) places a significant burden on healthcare systems. New Zealand has a high incidence of Sa-SSTI, and here most morbidity is caused by a polyclonal methicillin-susceptible (MSSA) bacterial population. However, MSSA also colonise asymptomatically the cornified epithelia of approximately 20% of the population, and their divide between commensalism and pathogenicity is poorly understood. We aimed to see whether MSSA are genetically differentiated across colonisation and SSTI; and given the close interactions between people and pets, whether strains isolated from pets differ from human strains. Methods: We compared the genomes of contemporaneous colonisation and clinical MSSA isolates obtained in New Zealand from humans and pets. Results: Core and accessory genome comparisons revealed a homogeneous bacterial population across colonisation, disease, humans, and pets. The rate of MSSA colonisation in dogs was comparatively low (5.4%). Conclusions: In New Zealand, most Sa-SSTI morbidity is caused by a random sample of the colonising MSSA population, consistent with the opportunistic infection model rather than the paradigm distinguishing strains according to their pathogenicity. Thus, studies of the factors determining colonisation and immune-escape may be more beneficial than comparative virulence studies. Contact with house-hold pets may pose low zoonotic risk.